Evaluation of the relationship between sick building syndrome complaints among hospital employees and indoor environmental quality - Sayan, Halil Erkan; Dülger, Seyhan (La Medicina del Lavoro, 2021)
Background: Sick building syndrome (SBS) is defined as a condition occurring in people who live or work in a modern building and who suffer from complaints such as headache, fatigue, lack of concentration, and irritation of the skin and mucous membranes. Objectives: The aim of this study is to examine the complaints associated with SBS in the employees of our hospital and evaluate the relationship between the characteristics of the work environment and the complaints of SBS. Methods: 890 workers participated in the study. The complaints of the participants were rated and the sum of all complaints was recorded as the Total Complaint Score (TCS). The mean TCS of the participants was compared according to demographic characteristics and work environment characteristics. Results: The most common complaints among the employees were fatigue (40%), and general muscle and joint pain (31.4%). There was a statistically significant difference in TCS according to the position (p < 0.001). The mean TCS was significantly higher in females [13 (0–81)] than in males [6 (0–59)] (p < 0.001). The mean TCS increased with the presence of odor, new wall paint, the presence of fungus/ mold on walls, and the presence of rotting/mold smell (p < 0.001, for all). TCS positively correlated with stress level, social relationship, noise level, comfort, cleanliness, number of employees in the same room, presence of odor, new wall paint, presence of rotting/mold, and use of chemical materials for cleaning in the room (p < 0.001, for all), and negatively correlated with room size and number of windows (p = 0.006, p < 0.001, respectively). Discussion: The present study found that the female gender, a high level of education, a high level of stress, a low level of social relationships and work environment characteristics were associated with the complaints of SBS among the employees. Accordingly, we believe that hospital management should be informed in order for the managers to take precautions and make new regulations.